Estrutura e dinâmica de perfilhamento do capim-marandu submetido a três intensidades de pastejo - Santana, Sabrina Saraiva [UNESP] (2015)
This study was carried out in order to assess and identify the effects of the grazing intensities in the water and in the water-drought transition periods on the structural characteristics of the sward and on the tillering dynamics in pastures of Brachiaria brizantha (Hochst ex. A. Rich.) cv. Marandu, within two consecutive years. The experimental period was from December 2010 to June 2014. The experiment was performed in a complete randomized block design, with repeated measurements in time. The treatments in the water period corresponded to the grazing intensities characterized by the average pasture heights (15, 25, and 35 cm). However, in the water-drought transition period they corresponded to the height records in the water. The assessed variables were: basal tiller appearance rate (TAR), basal tiller death rate (TDR), vegetative tiller density (TD), foliage area index (FAI), light interception (LI), total forage mass (TF), green foliage blade mass (GFB), green stem mass (GS), dead material mass (DM), relation leaf:stem (L/S). Greater TF, GFB, GS, FAI, and LI were observed in the water period in 2011 in relation to the water period in 2012. All variables increased with the increase in the sward height, except the L/S that reduced with the increase in the height of the water in 2011. The LI only presented year effect on the pastures managed at 15 cm of height, which greater LI was observed in the water period in 2011.The Marandu palisade grass presented increase in the TAR in pastures managed at 15 cm in relation to the ones managed at 25 and 35 m in the water period. The value of the DT increased at the height of 35 cm (23.9%) in relation to the ones managed at 25 (12.4%) and 15 (13.8%) cm of height in the water in 2011.The TAR was in average 63.3% greater in the water period in 2011 (36.8%) in comparison the 2012 (13.4%) and the TDR was greater (29.3%) in the water period in 2012 in comparison to 2011 (12.4%) only in the pastures ...